Wood and sediment storage and dynamics in river corridors. Issue 1 (19th February 2016) - Wohl, Ellen; Scott, Daniel N.
Abstract: Large wood along rivers influences entrainment, transport, and storage of mineral sediment and particulate organic matter. We review how wood alters sediment dynamics and explore patterns among volumes of in‐stream wood, sediment storage, and residual pools for dispersed pieces of wood, logjams, and beaver dams. We hypothesized that: volume of sediment per unit area of channel stored in association with wood is inversely proportional to drainage area; the form of sediment storage changes downstream; sediment storage correlates with wood load; the residual volume of pools created in association with wood correlates inversely with drainage area; and volume of sediment stored behind beaver dams correlates with pond area. Lack of data from larger drainage areas limits tests of these hypotheses, but the analyses suggest that sediment volume correlates positively with drainage area and wood volume. The form of sediment storage in relation to wood appears to change downstream, with wedges of sediment upstream from jammed steps most prevalent in small, steep channels and more dispersed sediment storage in lower gradient channels. Pool volume correlates positively with wood volume and negatively with channel gradient. Sediment volume correlates well with beaver pond area. More abundant in‐stream wood and beaver populations present historically equated to greater sediment storage within river corridors and greater residual pool volume. One implication of these changes is that protecting and re‐introducing wood and beavers can be used to restore rivers. This review of the existing literature on wood and sediment dynamics highlights the lack of studies on larger rivers. Copyright © 2016 John Wiley & Sons, Ltd.